2022
DOI: 10.1159/000528640
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiotherapy in Early-Stage Breast Cancer in Neoadjuvant and Exclusive Settings: A Systematic Review

Abstract: Introduction Breast cancer (BC) is one of the most common tumours, better screening policies and multidisciplinary approach allow personalised treatment. Radiotherapy (RT) plays a central role in the multimodal approach in BC, and recent evidence have shown the non-inferiority of hypofractionated treatments. The aim of this study is to describe the feasibility and validity of stereotactic RT (SBRT) in BC in neoadjuvant and exclusive setting. Methods A Pubmed/MEDLINE and Embase systematic review was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…TONIC trial demonstrated that SBRT (24Gy/3f) combined with nivolumab can increase the proportion of patients free of progression at 24 weeks than nivolumab alone (17% vs 8%) (Voorwerk et al, 2019). Another small sample research has indicated that preoperative with neoadjuvant chemotherapy may result in fair pCR rates of 36%, with the maximum response (pCR 67%) was obtained at a dose of 25.5Gy/3f (Bondiau et al, 2013), as well as no increase in the incidences of early or late-term adverse events (AEs) (Piras et al, 2023;Takanen et al, 2022). Together, these studies suggested SBRT may have strong immunomodulatory effects, rendering a synergistic antitumor effect with immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TONIC trial demonstrated that SBRT (24Gy/3f) combined with nivolumab can increase the proportion of patients free of progression at 24 weeks than nivolumab alone (17% vs 8%) (Voorwerk et al, 2019). Another small sample research has indicated that preoperative with neoadjuvant chemotherapy may result in fair pCR rates of 36%, with the maximum response (pCR 67%) was obtained at a dose of 25.5Gy/3f (Bondiau et al, 2013), as well as no increase in the incidences of early or late-term adverse events (AEs) (Piras et al, 2023;Takanen et al, 2022). Together, these studies suggested SBRT may have strong immunomodulatory effects, rendering a synergistic antitumor effect with immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…SBRT has already been widely applied to advanced breast cancer as salvage treatment targeting to osseous and brain metastasis or other oligometastatic sites (Nicosia et al, 2022;Viani et al, 2021). Preoperative SBRT may be advantageous for downstaging the tumor to enable breast conservation and improving pCR rate (Piras et al, 2023), with multiple trials investigating neoadjuvant SBRT in various malignancies (Holyoake et al, 2021;Kishi et al, 2020;Liu et al, 2022;Novikov et al, 2021) are currently ongoing. In addition, preclinical evidence suggested that SBRT has immunomodulatory properties by inducing cancer cells necrosis and releasing neoantigens to boost neoantigen-specific immune response and upregulate the expression of PD-L1 on tumor cells (Deng et al, 2014;Han et al, 2022;Park et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Piras et al 35 explored the potential of stereotactic radiotherapy (SBRT) in treating early stage BC in a neoadjuvant setting. The research analyzed multiple studies and underscored the feasibility and effectiveness of SBRT in a neoadjuvant context, noting its advantages such as lower toxicity rates and reduced treatment volumes.…”
Section: Neoadjuvant Radiotherapymentioning
confidence: 99%
“…Although NART has not been proven to decrease overall patients’ survival ( 42 ), the benefits have been demonstrated by the improvement in DFS in estrogen receptor-positive tumors ( 42 ). Significantly, the stereotactic RT approach provides a more accurate target for tumor treatment, leading to an increase in the percentage of conservative breast surgeries ( 43 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%